Characterization of the chloroplast genome of Ixonanthes chinensis (Ixonanthaceae). Issue 1 (2nd January 2019) - Zhi, Xueke; Tan, Guangwen; Hu, Zhenyang; Wang, Yongqi; Zhou, Qiujie; Wu, Wei; Zhou, Renchao
Abstract: Ixonanthes chinensis ( Ixonanthaceae ) is an endangered tree species distributed in South China and Vietnam. The phylogenetic position of Ixonanthes in the order Malpighiales remains controversial. Here we reported and characterized the complete chloroplast genome sequence of I. chinensis assembled from Illumina sequencing reads. The chloroplast genome size is 155, 296 bp, containing a large single copy (LSC) region of 83, 829 bp, a short single copy (SSC) region of 18, 917 bp, and a pair of inverted repeats (IRs) of 26, 275 bp. We predicted a total of 139 genes, which included 87 protein-coding genes, 44 tRNA genes, and 8 rRNA genes. Phylogenetic analysis showed that I. chinensis was sister to Linum usitatissimum from the family Linaceae rather than Erythroxylum novogranatense from the family Erythroxylaceae.